Giant aneurysm of the azygos pericallosal artery: Case report and review of the literature - Topsakal, C; Ozveren, F; Erol, FS; Cihangiroglu, M; Cetin, H (Elsevier Science Inc, 2003)
BACKGROUND Pericallosal aneurysms are encountered less than 6.7%, and giant aneurysms among them even less. Giant azygos pericallosal artery aneurysm at the callosomarginal bifurcation is extremely rare, and our case presented herein is the second one. The case is discussed with thorough review of the literature. METHODS A 65-year-old woman presented with an extremely rare giant aneurysm on the azygos pericallosal artery manifesting as subarachnoid hemorrhage in World Federation of Neurosurgical Societies Grade 3. Computed tomography (CT), magnetic resonance angiography (MRA), and four vessel angiography revealed a giant azygos pericallosal artery aneurysm associated with a second aneurysm at the left M1. RESULTS After recovery to Grade 2, she underwent surgery via the right frontal interhemispheric approach for the azygos artery aneurysm on the 17th day after bleeding. The true dimensions of the aneurysm were greater than indicated by angiography because of partial thrombosis. Trilobulate aneurysm was carefully dissected from the surrounding structures. Postoperative cerebral angiography showed no filling of the clipped aneurysm and preservation of circulation. CONCLUSION The treatment of distal anterior cerebral artery aneurysms is often difficult, because of their broad-based irregular configurations and adherence to surrounding tissue, tendency to bleed irrespective of size and the coexistence of other cerebral aneurysms. However, excellent outcomes can be obtained based on thorough preoperative radiologic evaluation, including magnetic resonance imaging (MRI), and correct selection of surgical approach. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: azygos pericallosal artery; cerebral aneurysm; cerebral angiography; distal anterior cerebral artery; pericallosal aneurysm